Agonist activation of estrogen receptor beta (ERβ) sensitizes malignant pleural mesothelioma cells to cisplatin cytotoxicity - Pinton, Giulia (BioMed Central, 2014)
BACKGROUND: Estrogen receptor (ER) β acts as a tumor suppressor in malignant mesotheliomas. METHODS: Here we explored the anti-proliferative and anti-tumorigenic efficacy of the selective ERβ agonist, KB9520, in human mesothelioma cell lines in vitro and in a mesothelioma mouse model in vivo. RESULTS: KB9520 showed significant anti-proliferative effect in ERβ positive human malignant pleural mesothelioma cells in vitro. Selective activation of ERβ with KB9520 sensitized the cells to treatment with cisplatin, resulting in enhanced growth inhibition and increased apoptosis. Furthermore, in CD1 nude mice mesothelioma tumor growth was significantly inhibited when KB9520 was added on top of the standard of care chemo combination cisplatin/pemetrexed, as compared to the cisplatin/pemetrexed alone group. Importantly, KB9520 exerted a protective effect to cisplatin toxicity in the non-malignant mesothelium derived MET5A cells. CONCLUSIONS: Together, the data presented suggest that selective targeting of ERβ may be an efficacious stand-alone treatment option and/or become an important add-on to existing malignant mesothelioma therapy. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/1476-4598-13-227) contains supplementary material, which is available to authorized users.